《长津湖》电影中的修辞手法分析GAYA BAHASA DALAM FILM “THE BATTLE AT CHANGJIN LAKE” YANG DISUTRADARAI CHENG CHENG KAI GE, TSUI HARK DAN DANTE LAM - Yuliandre Wijaya (Journal of Language, Literature and Teaching, 2022)
This study aims to find out the types of language styles and the factors in language style usage used in the film The battle at Changjin Lake directed by Cheng kai ge, Tsui Hark and Dante lam. Language style is a way of expressing thoughts through language in a unique way by choosing appropriate words and combining them in certain sentence structures, in order to create new and fresh ways of conveying. The design of this study is descriptive qualitative with documentation data collection techniques. The results of the data analysis show that there are 6 types of language styles, namely 3 styles of Jièdài (Metonymic), 7 styles of Fǎnwèn (Erotesis), 2 styles of Duì'ǒu (Antithesis), 1 style of Páibǐ (Parallelism), 4 styles of Fǎnfù ( Repetition), 3 styles of Shè wèn (Rhetorical) . The style of language most often used is Fǎnwèn (Erotesis). The results of the data analysis also show that the factors causing the usage of these language styles in the film are a person's identity, work, external environment, mood, time and location. The factor that causes the most language style usage is the external environment, so that the audience can feel that environment.Keywords: Film, Language Style, The Battle of Chang Lake